Seismic Waves Scattering Impact through Tunnel Excavation on Adjacent Monuments Subjected to Far Field Earthquakes - Ehsan Ghobakhloo; Mahyar Pourlak; Arash Razmkhah (Civil Engineering Dimension, 2015)
The study of the effect of seismic wave scattering has attracted extensive attention in the past couple of decades especially in infrastructures like tunnels. A seismic wave, meeting the tunnel, can generate scattering which, in most cases, may incur damages in adjacent structures. In this study, using Finite Element Method (FEM), the effect of seismic wave scattering in far field has been investigated. The twin tunnels of Shiraz subway system are selected as the case study in this research and three far field seismic waves were chosen for time history analyses. Investigating the normal mode (before tunnel construction) in comparison to the excavation mode (after tunnel construction) enables calculation of the effect of displacement in adjacent structures. The analysis results indicate there is a significant difference between before and after tunnel construction (P-value<0.05). Accordingly, the influence of constructing a tunnel on adjacent surface structures is very important for tunnel design.